2013
DOI: 10.1021/op300296t
|View full text |Cite
|
Sign up to set email alerts
|

Development of Related HCV Protease Inhibitors: Macrocyclization of Two Highly Functionalized Dienyl-ureas via Ring-Closing Metathesis

Abstract: A novel assembly of two structurally related 14-membered ring macrocyclic hepatitis C virus protease inhibitors is presented. Key to their successful construction was an ultimate ring-closing metathesis step on the respective highly functionalized dienyl-ureas. In the case of IDX316, this procedure significantly outperformed the original macrocyclizations in terms of reaction conditions, impurity profile, product isolation, and basic efficiency metrics. Simple nonchromatographic purification methods achieved s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
0
36
0
3
Order By: Relevance
“…[25] Polymeric (oligomeric) impurities were removed via as ilica plug,f ollowed by crystallization of the macrocycle directly from the filtrate.N of urther improvements to the RCM step have been disclosed. [23] Thus,oligomerization was limited by installing the exocyclicq uinolinyl group Q prior to RCM. While IDX316 did not proceed into clinical trials,d evelopment work in its synthesis revealed the impact of hydroxy substitution on RCM yields.…”
Section: Danoprevir (6 0013 M)mentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Polymeric (oligomeric) impurities were removed via as ilica plug,f ollowed by crystallization of the macrocycle directly from the filtrate.N of urther improvements to the RCM step have been disclosed. [23] Thus,oligomerization was limited by installing the exocyclicq uinolinyl group Q prior to RCM. While IDX316 did not proceed into clinical trials,d evelopment work in its synthesis revealed the impact of hydroxy substitution on RCM yields.…”
Section: Danoprevir (6 0013 M)mentioning
confidence: 99%
“…While IDX316 did not proceed into clinical trials,d evelopment work in its synthesis revealed the impact of hydroxy substitution on RCM yields. [23] Thus,oligomerization was limited by installing the exocyclicq uinolinyl group Q prior to RCM. Yields were raised from around 40 %for 8ato nearly 90 %for 8b,albeit at amaximum concentration of 0.008 m.…”
Section: Danoprevir (6 0013 M)mentioning
confidence: 99%
“…In yet one final example from the HCV protease area, process development efforts have been reported for two closely-related 14-membered ring macrocycles, IDX316 (266) and IDX320 (60). 348 Again, RCM was the cyclization method of choice. Due to numerous deficiencies within the original medicinal chemistry method, two alternative routes were investigated with the strategy ultimately modified such that the RCM became the final step, in contrast to the initial approach in which the RCM was executed much earlier in the synthetic scheme.…”
Section: Synthesis At Scalementioning
confidence: 99%
“…If not removed, these residues can causet he decomposition or isomerization of the product over time or negatively affect the yield of subsequent steps of the synthesis. Additionally,t hey preclude the use of such products in the synthesis of active pharmaceutical ingredients (API), [4][5][6][7][8][9][10] which are subjectt os trict legal limits on heavy-metal contamination (less than 10 ppm). [11] Thanks to the discoveryo fw ell-defined ruthenium catalysts Ru1-Ru6 (Figure 1), [12][13][14][15][16][17] olefin metathesis (OM) became av ery useful tool in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant product 4b contained 40 ppm of ruthenium (Table 1, entry 5). Scavengers I-III gave much better results (Table 1, entries [7][8][9][10][11][12][13][14][15][16][17][18][19]. The use of II (4.4 equiv) reduced the residual ruthenium content by two orders of magnitudew ith respect to the control experiment, down to 1.6 ppm ( Table 1, entry 12).…”
Section: Introductionmentioning
confidence: 99%